2015
DOI: 10.1142/s0217984914502686
|View full text |Cite
|
Sign up to set email alerts
|

Multi-index algorithm of identifying important nodes in complex networks based on linear discriminant analysis

Abstract: The evaluation of node importance has great significance to complex network, so it is important to seek and protect important nodes to ensure the security and stability of the entire network. At present, most evaluation algorithms of node importance adopt the single-index methods, which are incomplete and limited, and cannot fully reflect the complex situation of network. In this paper, after synthesizing multi-index factors of node importance, including eigenvector centrality, betweenness centrality, closenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Figure 3 reports the speed-ups for a variable number of threads. We find that speed-ups scale-up sublinearly for a small number of threads (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), but quickly reach a limit, as induced by the available number of processing units (40 in our case) and overhead for merging the parallel sub-results. Overall, parallelization offers constant speed-up at best, i.e.…”
Section: E Experimental Setupmentioning
confidence: 82%
See 2 more Smart Citations
“…Figure 3 reports the speed-ups for a variable number of threads. We find that speed-ups scale-up sublinearly for a small number of threads (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), but quickly reach a limit, as induced by the available number of processing units (40 in our case) and overhead for merging the parallel sub-results. Overall, parallelization offers constant speed-up at best, i.e.…”
Section: E Experimental Setupmentioning
confidence: 82%
“…The exact ranking of nodes from higher exact betweenness to lower exact betweenness is R1 = [8,18,13,17,4,10,7,6,15,9,5,2,19,16,3,14,1,12,11,20]. If we use RAND1_4 (sampling four pivots), we can get an estimated ranking R2 = [8,4,17,18,10,7,6,9,13,5,15,14,19,3,2,12,1,11,16,20]. If we only consider Top-1%-Hits (only one node in this small network), this method can get 100% accuracy as it correctly identify Node 8.…”
Section: Measures For Estimating the Quality Of Betweenness Approxmentioning
confidence: 99%
See 1 more Smart Citation
“…In complex networks, researchers always identify the important nodes using several evaluation metrics [37] . The representative metrics includes degree centrality (BC), closeness centrality (CC), betweenness centrality (BC) [38] , eigenvector centrality (EC) [39] , current flow closeness centrality (CCC) [40] , and load centrality (LC) [41] .…”
Section: Diagnosis and Treatment Analysis Model Designmentioning
confidence: 99%
“…Based on the shortest path, Zheng et al [5] combined proximity and centrality to find important nodes and found through performance analysis that the method was more effective in finding important nodes. Hu et al [6] designed a multi-index method which integrated the centrality of feature vectors and degree centrality to recognize important nodes and found through simulation experiments that the algorithm was more reasonable and accurate. Wen et al [7] designed a "No Return" method for the importance evaluation of aviation network nodes and found that this method could effectively find potential important nodes with high accuracy after testing it on the aviation networks of China and the United States.…”
Section: Introductionmentioning
confidence: 99%